CHILD-FRIENDLY VEGETARIAN FOOD PACKAGING: VISUAL SAFETY, NUTRITION COMMUNICATION & ECO-MATERIALS — A QUALITATIVE STUDY OF VISUAL ELEMENTS IN FIVE INDIAN FOOD PRODUCTS - Wadhawan, Tanisha; Singh, Vinay; Singh, Arjita; Mishra, Priya; Gautam, Sachiv; Awasthi, Mohit (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The packages are a powerful and effective verbal and visual tool, which influences children preferences and parent’s attitudes toward the safety, nutrition and ethics of the products. Since the Indian market of vegetarian food aimed at kids is expanding, the packaging design gains additional significance due to the conservative standards of diet and increased focus on health and sustainability. This qualitative research explores the significance of the basic visual details namely color, typeface and illustration in five Indian vegetarian food products that were designed to appeal to children. The study employs both visual semiotic and thematic analysis to examine the message conveyed through packaging in terms of food safety, nutritional transparency and environmental material awareness. The findings indicate that bright and warm colors are employed to derive the attention of kids whereas soft and natural colors are employed to demonstrate to the parents that the product is safe and healthy. This supports previous research on the role of color in food packaging with regard to emotions Heller et al. (2019), Martin and Singh (2023). Children will be more attracted when the type is entertaining and parents will feel more knowledge about the nutritional information in case the type is structured and is easy to read. This aligns with studies on the way to structure information in terms of packaging design Peters et al. (2020). Illustrations, especially friendly characters and pictures of ingredients also play the role of two-way communicators: they attract the interest of children and reinforce gradually arguments about vegetarianism and health Nguyen and Jha (2024). However, the eco-material communication is not that well represented yet, and this is why the ability of sustainability signaling can still be improved Kumar and Ghosh (2022). The research provides design-based guidance to creating child-friendly vegetarian food packaging, which is aesthetically pleasing, has a clear nutritional value and is friendly to the environment, leading to practical implications to designers of food, food manufacturers, and nutrition communication based on policies.